Does gender influence quality of life in children with atopic dermatitis? - Janković, Slavenka; Ražnatović Đurović, Milena; Ćirković, Anđa; Janković, Janko (Scripta Medica, 2019)
Introduction: Atopic dermatitis (AD) is a chronic skin disease that has a significant impact on quality of life (QoL). The aim of this paper was to evaluate if gender affects some aspects of QoL in children with AD. Materials and methods: The cross-sectional study was conducted at the Clinic of Dermatology and Venereology, Clinical Center of Montenegro, between August 2017 and July 2018 and included 200 children aged 5−16 years with AD diagnosis. The severity of disease was measured by the Three Item Severity (TIS) score, while QoL was assessed with the Children’s Dermatology Life Quality Index (CDLQI). Socio-demographic data on children with AD were collected by a short questionnaire. Results: The difference in overall CDLQI between boys and girls was not statistically significant. The domains that were most affected by AD were school/holidays (mean score 2.27 ± 0.65), and symptoms (mean score 2.22 ± 0.70). Swimming/sports activities, school/holidays, teasing/bullying and sleep disturbance were more affected in girls. Overall CDLQI score and CDLQI subscale scores (except school/holidays and sleep in boys) significantly correlated with TIS. According to multivariate logistic regression analyses statistically significant differences between two genders were not found for age, AD severity, concomitant atopic disease, and family history of atopic disease. Conclusion: Although we did not find differences between the two genders in the overall health related QoL, this study confirmed the tendency for AD to have a more severe impact on girls’ lives. These results may influence treatment and counselling of children affected with AD.